PENERAPAN PEMBELAJARAN EKSPERIENSIAL DALAM MENGEMBANGKAN SELF-REGULATED LEARNING - Darmiany Darmiany (Universitas Negeri Malang, 2016)
Abstract: Implementing Experiential Learning to Promote Students' Self-regulatedness. This study tries to investigate how experiential learning can promote students' Self-regulatedness. A classroom action research has incorporated training and the utilization of meta-cognition, motivation and learning behaviour that was believed to be effective since it epitomizes the behaviour of a life-long learner. It could be concluded that implementation of this classroom action research had progressively approximated the criterion of success in three cycles. More and more students became highly motivated to make the best journal possible which has also affected the quality of their learning activities in doing independent study by seeking additional reference, holding discussions with classmates, and submitting more useful topics. Abstrak: Penerapan Pembelajaran Eksperiensial dalam Mengembangkan Self-Regulated Learning. Penelitian ini bertujuan untuk menerapkan pembelajaran eksperiensial agar mahasiswa menggunakan self-regulated learning (SRL) dalam belajar. Penelitian tindakan kelas tiga siklus dilakukan terhadap satu kelas Perkembangan Peserta Didik (52 mahasiswa) di Universitas Negeri Malang. Belajar eksperiensial melalui empat tahap secara siklikal yaitu concrete experience, reflective observation, abstract conceptualization, dan active experimentation berhasil membantu mahasiswa untuk menerapkan SRL dalam belajar. Siklus pertama, 88,5% mahasiswa tidak menggunakan SRL dalam belajar. Siklus kedua penggunaan SRL meningkat mencapai 87%. Peningkatan cukup signifikan terjadi pada siklus ketiga,yakni mencapai 94,2%.